Study on the Key Influential Factors on Water Huff-n-Puff in Ultralow-Permeability Reservoir. (29th August 2021) - Wang, Xiaoyan; Xie, Kun; Zhang, Jie; Zhang, Yong; Zhang, Yang; Wang, Wei; Yan, Xi; Zhao, Fengxiang
Abstract : Ultralow-permeability reservoirs are difficult to effectively develop using conventional technologies, so it generally produces using horizontal wells' volume fracturing. Besides, oil wells also face the problems of short stable or no production period, rapid decline rate, and extremely low development degree. Water huff-n-puff of oil recovery technology is a quality and efficiency technology to improve the development effect of an ultralow-permeability reservoir. A systematic study on the related key influential factors of water huff-n-puff is done for improving the development effect of ultralow-permeability reservoirs. This manuscript studied the key influential factors of water huff-n-puff and related improving recovery methods using physical simulation experiments to put forward a beneficial condition for water huff-n-puff, combining with the field practice. The results show that imbibition and energy supplement are main mechanisms of water huff-n-puff; imbibition oil recovery is influenced by rock wettability, permeability, boundary condition, fracture length, water injection speed, and imbibition solution type; the stronger the water-wet reservoir rock is, the bigger the core permeability is, the longer the fracture length is, the larger the contacting area between imbibition solution and rock is, the stronger the ability of imbibition solution to change wettability, and to reduce the interfacial tension force between oil and water is, the better effect of water huff-n-puff is. So far, the field practice of water huff-n-puff has been conducted in 38 wells; the success rate can reach 92.1%, cycle oil increment of single well can reach 972 t, and accumulated oil in evaluation period can reach 36936 t, which further proves that water huff-n-puff can achieve a good effect. The effective methods to improve the development effect of an ultralow-permeability reservoir are changing reservoir physical property and supplying reservoir energy. Higher reservoir energy is good for oil flow, and better physical property can improve the displacement effect and imbibition function of injection solution. Artificial fracturing, higher injection-production ratio, and pretreatment of temporary stoppage fracturing are good methods to improve the development effect of water huff-puff.